Screening the Pathogen Box for Identification of New Chemical Agents with Anti-Fasciola hepatica Activity. - Machicado, C. (2021)
Fascioliasis is an infectious parasitic disease distributed globally and caused by the liver fluke Fasciola hepatica or F. gigantica. This neglected tropical disease affects both animals and humans, and it represents a latent public health problem due to the significant economic losses related to its effects on animal husbandry. For decades, triclabendazole has been the unique anti-Fasciola drug that can effectively treat this disease. However, triclabendazole resistance in fascioliasis has more recently been reported around the world, and thus, the discovery of novel drugs is an urgent need. The aim of this study was to investigate the fasciocidal properties of 400 compounds contained in the Pathogen Box. The first stage of the screening was carried out by measuring the fasciocidal activity on metacercariae at a concentration of 33 M each compound (the standard dose). Subsequently, the activities of the most active compounds (n 33) at their 50% inhibitory concentration (IC50) values against metacercariae were assayed, and the results showed that 13 compounds had IC50s of 10 M. The second stage queried the activities of these compounds at 33 M against adult flukes, with seven of the compounds producing high mortality rates of 50%. Four hit compounds were selected on the basis of their predicted nontoxic properties, and the IC50 values obtained for adult worms were 10 M; thus, these compounds represented the best fasciocidal compounds tested here. A cytotoxicity assay on four types of cell lines demonstrated that three compounds were nontoxic at their most active concentration. In conclusion, three hit compounds identified in this proof-of-concept study are potential candidates in the discovery of new fasciocidal drugs. Further studies are warranted.